2021
DOI: 10.2147/jir.s298242
|View full text |Cite
|
Sign up to set email alerts
|

Coronil, a Tri-Herbal Formulation, Attenuates Spike-Protein-Mediated SARS-CoV-2 Viral Entry into Human Alveolar Epithelial Cells and Pro-Inflammatory Cytokines Production by Inhibiting Spike Protein-ACE-2 Interaction

Abstract: Purpose Coronil is a tri-herbal formulation containing extracts from Withania somnifera, Tinospora cordifolia, and Ocimum sanctum . Recently, it was shown that Coronil rescued humanized zebrafish from SARS-CoV-2 induced pathologies. Based on reported computational studies on the phytochemicals present in Coronil, it could be a potential inhibitor of SARS-CoV-2 entry into the host cell and associated cytokines’ production. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 63 publications
0
30
0
Order By: Relevance
“…It could hamper the interface of ACE-2 with SWT (wild-type S protein) and also with SD614G (more infectious variant). The elevated level of IL-6, IL-1β, and TNF-α in A549 cells also reduced after treatment with Coronil 96 . In another research investigation, Balkrishna et al, performed the analytical evaluation of Divya-Swasari-Vati, which is a herbal medication containing calcium prepared for providing relief from the respiratory symptoms due to corona infection.…”
Section: Recent Evidence Of Uses Of Herbs For Covid-19mentioning
confidence: 87%
“…It could hamper the interface of ACE-2 with SWT (wild-type S protein) and also with SD614G (more infectious variant). The elevated level of IL-6, IL-1β, and TNF-α in A549 cells also reduced after treatment with Coronil 96 . In another research investigation, Balkrishna et al, performed the analytical evaluation of Divya-Swasari-Vati, which is a herbal medication containing calcium prepared for providing relief from the respiratory symptoms due to corona infection.…”
Section: Recent Evidence Of Uses Of Herbs For Covid-19mentioning
confidence: 87%
“…Observations from a randomized placebo controlled pilot clinical study, that evaluated the effectivity of these medicines on a slightly larger asymptomatic to mildly symptomatic patient pool, upholds our findings from this study ( Devpura et al, 2021 ). For better patient compliance, AC, GG and TG were combined and formulated into a tablet, called ‘Coronil’ and subsequently, its pharmacological effects against SARS-CoV-2 spike protein have been confirmed through in-vitro (( Balkrishna et al, 2021a ) and in-vivo ( Balkrishna et al, 2020c ) studies.…”
Section: Discussionmentioning
confidence: 99%
“…Extract of Prunella vulgaris and our formulation share critical phytoconstituents, such as Quercetin, Ursolic acid, Saponins, Caffeic acids, Rosmarinic acid, Luteolin, Kaempferol, Gallic acid, etc. Furthermore, the study by Balkrishna et al, 2021, showed the herbal drug named Coronil effectively inhibited the interaction of ACE-2 with the wild-type S protein (SWT) and also prevented the SARS-CoV-2 S-protein pseudotyped vesicular stomatitis virus (VSVppSARS-2S) mediated cytokine response in these cells by reducing entry of pseudoviruses into host cells [ 44 ].…”
Section: Discussionmentioning
confidence: 99%